Psoriasis in a patient with dermatomyositis - Pavlović Miloš D.; Zečević Radoš D.; Zolotarevski Lidija (Vojnosanitetski Pregled)
Psoriasis has been consistently associated with arthritis and inflammatory bowel diseases, though there have been reports on patients with psoriasis and other autoimmune dermatoses. Sometimes, sharply demarcated scaly plaques located over extensor surfaces in patients with dermatomyositis may clinically resemble psoriatic lesions. Histologic findings of interface dermatitis, typical for dermatomyositis, help clinicians to rule out psoriasis. A patient is presented with dermatomyositis in which psoriatic lesions developed over the extremities and lower trunk. Histological examination confirmed the diagnosis of psoriasis. Both diseases have run independent courses. It is prudent to include psoriasis in the differential diagnosis of scaly eruptions occurring in dermatomyositis patients.